A novel mutation in the succinate dehydrogenase subunit D gene in siblings with the hereditary paraganglioma–pheochromocytoma syndrome. (6th October 2014) - Prasad, Chaithra; Oakley, Gerard J; Yip, Linwah; Coyne, Christopher; Rangaswamy, Balasubramanya; Dixit, Sanjay B
Germline mutations in the succinate dehydrogenase complex subunit D gene are now known to be associated with hereditary paraganglioma–pheochromocytoma syndromes. Since the initial succinate dehydrogenase complex subunit D gene mutation was identified about a decade ago, more than 131 unique variants have been reported. We report the case of two siblings presenting with multiple paragangliomas and pheochromocytomas; they were both found to carry a mutation in the succinate dehydrogenase complex subunit D gene involving a substitution of thymine to guanine at nucleotide 236 in exon 3. This particular mutation of the succinate dehydrogenase complex subunit D gene has only been reported in one previous patient in Japan; this is, therefore, the first report of this pathogenic mutation in siblings and the first report of this mutation in North America. With continued screening of more individuals, we will be able to create a robust mutation database that can help us understand disease patterns associated with particular variants and may be a starting point in the development of new therapies for familial paraganglioma syndromes.